Detailed Dissection of UBE3A-Mediated DDI1 Ubiquitination - Elu, Nagore; Osinalde, Nerea; Beaskoetxea, Javier; Ramirez, Juanma; Lectez, Benoit; Aloria, Kerman; Rodriguez, Jose Antonio; Arizmendi, Jesus M.; Mayor, Ugo (Frontiers in Physiology, 2019)
The ubiquitin E3 ligase UBE3A has been widely reported to interact with the proteasome, but it is still unclear how this enzyme regulates by ubiquitination the different proteasomal subunits. The proteasome receptor DDI1 has been identified both in Drosophila photoreceptor neurons and in human neuroblastoma cells in culture as a direct substrate of UBE3A. Here, we further characterize this regulation, by identifying the UBE3A-dependent ubiquitination sites and ubiquitin chains formed on DDI1. Additionally, we found one deubiquitinating enzyme that is capable of reversing the action of UBE3A on DDI1. The complete characterization of the ubiquitination pathway of an UBE3A substrate is important due to the role of this E3 ligase in rare neurological disorders as Angelman syndrome.